GDF11 Attenuated ANG II-Induced Hypertrophic Cardiomyopathy and Expression of ANP, BNP and Beta-MHC Through Down-Regulating CCL11 in Mice - Zhang, Chenjun; Wang, Ying; Ge, Zhiru; Lin, Jie; Liu, Jiwen; Yuan, Xiaofei; Lin, Zijun (Current Molecular Medicine, 2018)
Background: Growth differentiation factor 11 (GDF11) decreases with age, and increased C-C motif chemokine 11 (CCL11) is involved in aging. However, the effects of GDF11 on Angiotensin II (ANG II)-induced hypertrophic cardiomyopathy and expression of markers for volume overload and hypertrophy such as ANP, BNP and beta-MHC, as well as the relationship between GDF11 and CCL11 in hypertrophic cardiomyopathy are unclear. Therefore, the current study aimed to examine the effects of GDF11 on ANG II-induced hypertrophic cardiomyopathy and expression of ANP, BNP and beta-MHC in mice, and explore possible molecular mechanisms. Methods: Vectors were constructed and viruses were packaged. Mouse cardiomyocytes were treated with ANG II for 24 h. Meanwhile, mouse cardiomyocytes were divided into 4 groups: (1) control; (2) ANG II; (3) ANG II+GDF11; and (4) ANG II+CCL11. Furthermore, mouse cardiomyocytes were treated with GDF11 and CCL11 proteins for 48 h, respectively. The thickness of IVS and LVPS during systole and diastole were measured by cardiac ultrasound in the mouse model of hypertrophic cardiomyopathy. The relative expression of ANP, BNP, beta-MHC, CCL11 and GDF11 in cardiomyocytes or heart tissue of mice was detected by qPCR or Western blot. 3’- UTR luciferase reporter assay was utilized to examine the relationship between GDF11 and the expression of CCL11. Results: The expression of ANP, BNP, and beta-MHC in mouse cardiomyocytes was significantly increased after the cells were treated with 800 nM ANG II, which was utilized in the following cell experiments. After ANG II treatment, 0.2 ng/ml GDF11 group displayed the highest inhibition of expression of ANP, BNP and beta-MHC in mouse cardiomyocytes, whereas 50 ng/ml CCL11 group displayed the highest stimulation of the expression. GDF11 at 10 ng/ml significantly decreased the expression of CCL11 in mouse cardiomyocytes as compared to the control group. Mice treated with ANG II had increased thickness of IVS and LVPS during both systole and diastole, which was significantly attenuated by GDF11 overexpression. GDF11 overexpression attenuated the increase in expression of ANP, BNP and beta-MHC in the mice model of hypertrophic cardiomyopathy. The relative serum concentration of GDF11 was markedly decreased, and CCL11 was dramatically increased in mice with hypertrophic cardiomyopathy. GDF11 overexpression restored the serum concentration of GDF11 and CCL11 in the mice model of hypertrophic cardiomyopathy. In addition, GDF11 interference group had markedly increased expression of CCL11, whereas GDF11 overexpression group had significantly decreased expression of CCL11 in luciferase reporter assay. Conclusions: GDF11 attenuated ANG II-induced hypertrophic cardiomyopathy and expression of ANP, BNP and beta-MHC through down-regulating CCL11 in mice.
Keywords: beta-MHC